“Controle sua língua”: uma análise discursiva fronteriza da escrit(ur)a no processo identitário da mulher chicana mestiza - Machado, João Paulo Ferreira Tinoco (2021)
This thesis proposes a study around the process of the identity construction of the Chicana/indigenous woman, from Gloria Anzaldúa’s writing on the book Borderlands/La frontera: the new mestiza (2012), especially the possible identity representations from the bio and geo that the subject is situated. Thus, it is necessary a critic of the knowledge/power studies (FOUCAULT, 2012), under the archaeology and genealogy methods; of the Fronteriza Discourse Analysis, which it allows the analyst seeks other links in the science field that might help with analyzing the corpus, mainly the decolonial studies. The goal is also to seek translation notions (DERRIDA, 2001a), from the mestiza`s perspective (ANZALDÚA, 2012) which it gives me support to use the double bind in the face of the impossibility of translation; and conceptions on Local Geostoric which considarates the subjects (bio), places (geo) and narratives (grafias) that are part of the fronterizo subject`s biographical landscapes (NOLASCO, 2013). From a decolonial option (ANZALDÚA, 2012; GUERRA, 2018; NOLASCO, 2013; ANZALDÚA, 2012; MIGNOLO, 2012), I intend to search in the writing produced by the Chicana/indigenous woman the silent identities which scape from the heteronormativity. My hypothesis is that from the position-subject of the Chicana/indigenous woman, under the fronterizo epistemology thinking, it exposes the herida relation between the human being, tongue and identity, that is, there are marks on the subject Chicana woman’s writing that overlap past marks/remains that reach other peoples, other subjects who experience the marginalization, constructing resistance and denouncement through discursive practices and the fronterizo identity. This thesis is divided into three parts, containing six chapters: in I. Pontes biográficas para atravessar o local fronterizo, I discuss around the Chicano subject, the discursive situation, the discursive memory and the interdiscourse; II. Dispositivos teóricos-metodológicos: o discurso fronterizo, a desconstrução e a descolonização, I articulate discursive and decolonial notions, the deconstruction and the archaeology and genealogy methods; Chapter III. A escrit(ur)a Zurda/traducao Mestiza is around the possibility and impossibility of translation, that is, the double bind to create the Mestiza Translation notion; In chapter IV, Em direcao ao pensamento fronterizo/mestizo, and V, (Des)atando os pontos da herida, I interpret the analytic process which I divide into four axes, they are: Dos modos de subjetivação do pensamento mestizo; Do discurso insurgente; A herida aberta como Resistência e existencia; and Os silenciamentos na tradução mestizo. In chapter VI. La Venadita e O Mar de Repolhos (A Sea of Cabbages), I present two poems written by Gloria Anzaldúa (2012), translated by me. The results highlight that Anzaldúa (2012) shows that being a woman in the margin, being a Chicana/indigenous, being lesbian is to occupy the in-between place to resist and exist. The work intends to bring contributions with possible unfoldings from different places of enunciation, even when we know that any discussion could not end the debates and the possibility of intersections that the theme around the social (in)equality may provoke in Human Science.